A new Holopothrips species (Thysanoptera: Phlaeothripidae) damaging Mollinedia (Monimiaceae) leaves in Southern Brazil - Cavalleri, Adriano; Kaminski, Lucas A. (Zootaxa, 2007)
A new species of leaf-feeding thrips is described, from the Atlantic Rain Forest in Rio Grande do Sul State, Southern Brazil. Holopothrips claritibialis sp. nov. differs from other species of the genus in the combination of the following characteristics: all tibiae predominantly yellow; maxillary stylets retracted near the postocular setae; metanotum with reticulation, elongated on anterior half and equiangular on posterior half; pelta with equiangular reticulation medially but weak or absent laterally and posteriorly; glandular areas present on sternites VII–VIII in males (usually three glandular areas on each sternite). This species causes deformations and rolls on leaves of Mollinedia schottiana. Some aspects of the biology and intraspecific variation of this species are discussed.